Medical student reporting of factors affecting pre-clerkship changes in empathy: a qualitative study - Sheikh, Hasan; Carpenter, Jennifer; Wee, Joy (Revue canadienne de l'éducation médicale, 2013)
Objective: To isolate factors that medical students identify as possibly affecting empathy in pre-clerkship years of medical school. Methods: 12 students in their second year of medical school at Queen’s University were randomly selected and asked to participate in semi-structured interviews conducted from an ethnographic perspective. Results: Students reported both negative and positive changes in empathy. Negative changes included desensitization and focusing on the disease process, decreased ability to see things from patients’ perspectives, and routine responses in emotional situations. These changes occur due to time constraints, objective lessons in empathy, and a changing identity. Positive changes included an increased awareness of the impact of illness, and increased ability to read feelings. These changes result from increased exposure to patients, discussions surrounding the psychosocial impact of illness, and positive role models. Conclusion: Students should be made aware of the limitations of objective lessons in empathy, and non-evaluated, implicit lessons should be emphasized when possible. Students should be encouraged to maintain relationships outside of medicine. Aspects of medical school that currently promote empathy should be reinforced, including exposure to patients, opportunities to work closely with positive role models, and practical discussions surrounding the psychosocial impact of illness.